Anti-TNF Agents in Behçet's Disease Treatment - Semih Tatlıcan, (Archives of Rheumatology, 2009)
Behçet's disease (BD) is a systemic vasculitis affecting all vessel types. The etiology and pathogenesis of the disease are not clearly known. Tumor necrosis factor α (TNF-α) is a major proinflammatory molecule that has been shown to have a critical role in the pathogenesis of BD. This role was also supported by the articles reporting the effectiveness of anti-TNF agents in the treatment of BD. Infliximab is the most widely used anti-TNF agent in the treatment of BD patients with manifestations of eye, central nervous system, gastrointestinal system, vascular system and joint involvements. Although infliximab seems to be more effective and faster than the other two agents in the treatment of all manifestations, the relative frequency of infusion reactions and the administration route may limit the usage of this drug. Etanercept was found to be more effective in the treatment of patients with mucocutaneous disease and arthritis compared to other manifestations. In spite of its effectiveness being determined in only a limited number of manifestations, the easy administration route of etanercept can be an advantage in selected indications. (Turk J Rheumatol 2009; 24: 27-38)